Princess diaries 2 royal engagement - Houston, Whitney; Chase, Debra Martin; Iscovish, Mario; Marshall, Garry; Walt Disney Pictures (Burbank, CA : Walt Disney Home Entertainment, 2004)
Princess Mia has just graduated college. She is soon going to take over as Queen of Genovia from her grandmother, Queen Clarisse. However, Mia learns that she must marry in 30 days or forfeit the crown of Genovia to another rightful heir, Nicholas Devereaux. His uncle, Vicount Mabrey is really the one who wants Nicholas to be King. Not trusting Nicholas, Mia picks a decent guy who's sweet and charming and likeable, but can she go through with the wedding to someone she doesn't really love?
Title from title screen
Subtitles in English, Chinese, Korean, Indonesian, Thai
Screenplay by Shonda Rhimes ; story, Gina Wendkos ; director of photography, Chales Minsky ; editor, Bruce Green ; music, John Debney ; costume designer, Gary Jones ; production designer, Albert Brenner
Casts: Julie Andrews, Anne Hathaway, Hector Elizondo, John Rhys-Davies, Heather Matarazzo, Chris Pine, Callum Blue, Kathleen Marshall, Tom Poston
Keywords: Princesses -- Drama; Marriage -- Drama; Man-woman relationships -- Drama; Comedy films